Liquidity Hoarding in Financial Networks: The Role of Structural Uncertainty - Stojan Davidovic; Amit Kothiyal; Mirta Galesic; Konstantinos Katsikopoulos; Nimalan Arinaminpathy (Complexity)
The dynamics of confidence affect a plethora of financial phenomena including liquidity hoarding. We present a multiagent model of a financial network in which confidence dynamics are shaped by structural uncertainty—that is, the lack of knowledge about the network of interbank cross-exposures. During a financial crisis, structural uncertainty makes it difficult for banks to assess the risk of financial contagion and their own health. Under such conditions, banks are more likely to behave conservatively and quickly act on information they receive from their local environment. A sudden financial shock, therefore, can be characterized by high-intensity local impact on confidence. We find that such local impacts quickly spread throughout the network, causing more damage than a shock that evenly affects all localities in the system; for example, a complete breakdown of the system occurs with a higher probability. The results are explained analytically by linking system performance to the speed of decrease in confidence.